2022
DOI: 10.1021/acs.jproteome.1c00912
|View full text |Cite
|
Sign up to set email alerts
|

Irradiation Causes Alterations of Polyamine, Purine, and Sulfur Metabolism in Red Blood Cells and Multiple Organs

Abstract: Investigating the metabolic effects of radiation is critical to understand the impact of radiotherapy, space travel, and exposure to environmental radiation. In patients undergoing hemopoietic stem cell transplantation, iron overload is a common risk factor for poor outcomes. However, no studies have interrogated the multiorgan effects of these treatments concurrently. Herein, we use a model that recapitulates transfusional iron overload, a condition often observed in chronically transfused patients. We applie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 65 publications
2
17
0
Order By: Relevance
“…A recent study revealed that abnormal cell metabolism promotes viral invasion 9 . Irradiation has great impacts on the metabolism of target cells and may affect SARS‐CoV‐2 invasion 12 . In this study, we confirmed for the first time, that irradiation induced a vulnerable cellular state for SARS‐CoV‐2.…”
Section: Introductionsupporting
confidence: 78%
“…A recent study revealed that abnormal cell metabolism promotes viral invasion 9 . Irradiation has great impacts on the metabolism of target cells and may affect SARS‐CoV‐2 invasion 12 . In this study, we confirmed for the first time, that irradiation induced a vulnerable cellular state for SARS‐CoV‐2.…”
Section: Introductionsupporting
confidence: 78%
“…82 Prior work in mice found an association between the levels of oxylipins, iron metabolism (the ferrireductase STEAP3) and poor post-transfusion recovery of stored RBCs. 83 Of note, another iron-dependent enzyme, 84 spermine oxidase (SMOX) was found to be polymorphic in routine blood donors, which was here associated with varying levels of the product of its enzymatic activity, the polyamine spermine.…”
Section: Discussionmentioning
confidence: 85%
“…In this view, it is worth noting that increases in kynurenine were accompanied by elevations in the levels of NAD+ − an essential cofactor for glycolysis and the Krebs cycle—but not picolinic acid, a neurotoxicant associated with neurocognitive disabilities in individuals with Trisomy 21 42 . On the other hand, elevated levels of indoles–tryptophan metabolites of microbial origin, 43 with a role in systemic responses to inflammation and oxidant stress 44 and their impact on the central nervous system 43 ‐ may be telling of a link between aberrant platelet metabolism in OM and systemic inflammation 45 and neurodegeneration 46 . Linking platelet metabolism to cognitive/behavioral function is not novel, in that platelet levels of serotonin (another tryptophan metabolite that is stored in platelet dense granules 47 and here elevated in OM donors) have long been associated with incidence and severity of depression secondary to deranged serotonin metabolism in the central nervous system 48 …”
Section: Discussionmentioning
confidence: 99%